Meningkatkan Mindset Entrepreneur Santri (Santripreneur) dalam Mewujudkan Kemandirian Ekonomi Pesantren - Iwan Henri Kusnadi; Tita Kartika Dewi; Varian Yudhiansyah; Yogi Sugiarto Maulana (Pusat Riset dan Inovasi Nasional, 2026)
Islamic boarding schools (pesantren) have great potential as centers for community-based economic empowerment, but the entrepreneurial mindset of students is often not optimally developed. This community service program aims to improve the entrepreneurial mindset of students at Al-Inayah Islamic Boarding School through experience-based training and intensive mentoring. The methods used include a participatory approach, interactive training, practical training on organic fertilizer production, strengthening Islamic entrepreneurial values, and mentoring in developing business ideas. This activity was attended by 30 students and evaluated using pre- and post-training instruments. The results showed a 36% increase in entrepreneurial mindset scores, accompanied by significant developments in creativity, risk-taking, and the ability to recognize market opportunities. The program also produced three initial business groups: organic fertilizer processing, agricultural product marketing, and agricultural equipment rental services, which serve as initial steps towards the economic independence of the Islamic boarding school. These findings confirm that experience-based training and ongoing mentoring are effective in shaping the entrepreneurial mindset of students and encouraging the optimization of the Islamic boarding school's productive assets as an effort to strengthen the economy based on Islamic values ​​and sustainability.